(untitled) (Altre Modernità, 2023)
Laurie Ruth Johnson (ed.), Germany from the Outside. Rethinking German Cultural History in an Age of Displacement (New York, Bloomsbury, 2022, 368 pp. ISBN 978-501-375-903) by Alessandra Goggio